Ultrafiltration of charge-stabilized dispersions at low salinity. Issue 20 (26th April 2016) - Roa, Rafael; Menne, Daniel; Riest, Jonas; Buzatu, Pompilia; Zholkovskiy, Emiliy K.; Dhont, Jan K. G.; Wessling, Matthias; Nägele, Gerhard
Abstract : Transport mechanisms in cross-flow ultrafiltration (left), and concentration-polarization and permeate flow profiles (right). Abstract : We present a comprehensive study of cross-flow ultrafiltration (UF) of charge-stabilized suspensions, under low-salinity conditions of electrostatically strongly repelling colloidal particles. The axially varying permeate flux, near-membrane concentration-polarization (CP) layer and osmotic pressure profiles are calculated using a macroscopic diffusion-advection boundary layer method, and are compared with filtration experiments on aqueous suspensions of charge-stabilized silica particles. The theoretical description based on the one-component macroion fluid model (OCM) accounts for the strong influence of surface-released counterions on the renormalized colloid charge and suspension osmotic compressibility, and for the influence of the colloidal hydrodynamic interactions and electric double layer repulsion on the concentration-dependent suspension viscosity η, and collective diffusion coefficient D c . A strong electro-hydrodynamic enhancement of D c and η, and likewise of the osmotic pressure, is predicted theoretically, as compared with their values for a hard-sphere suspension. We also point to the failure of generalized Stokes–Einstein relations describing reciprocal relations between D c and η . According to our filtration model, D c is of dominant influence, giving rise to an only weakly developed CP layer having practically no effect on the permeate flux. This prediction is quantitatively confirmed by our UF measurements of the permeate flux using an aqueous suspension of charged silica spheres as the feed system. The experimentally detected fouling for the largest considered transmembrane pressure values is shown not to be due to filter cake formation by crystallization or vitrification.